CENFED appointed as an Authorised Training Centre for Contractors by the Malaysian Construction Industry Development Board (CIDB) - Zainal, Bahari (Penerbit UMP, 2009)
Universiti Malaysia Pahang's (UMP) Centre for Continuing Education & Professional Development (CENFED) has obtained recognition from the government when it was appointed as an Authorised Training Centre for Contractors (PBLK) by the Malaysian Construction Industry Development Board (CIDB). With this appointment, CENFED has been given the task to train registered contractors as well as individuals who intend to get involved in the construction industry.